The prevalence, results, and treatments of the patients followed up with a diagnosis of metabolic disease in the pediatric intensive care unit: A single-center experience - Gültaç Evren; Ayşe Ergül Bozacı (Trends in Pediatrics)
Objective: Inborn errors of metabolism (IEM) are a rare, inherited, heterogeneous group of diseases that are mostly symptomatic in the pediatric age group. Late diagnosis and delays in intervention can result in acute metabolic decompensation, progressive neurological damage, or death. IEM patients are responsible for significantly increased morbidity and mortality in intensive care units. Rapid, aggressive, and supportive treatment in pediatric intensive care units can reduce morbidity and mortality in IEM patients.